Flexible and High‐Loading Lithium–Sulfur Batteries Enabled by Integrated Three‐In‐One Fibrous Membranes. Issue 38 (25th August 2019) - Wang, Jianan; Yang, Guorui; Chen, Jie; Liu, Yunpeng; Wang, Yuankun; Lao, Cheng‐Yen; Xi, Kai; Yang, Duowen; Harris, Christopher J.; Yan, Wei; Ding, Shujiang; Kumar, Ramachandran Vasant
Abstract: Lithium–sulfur batteries are appealing as high‐energy storage systems and hold great application prospects in wearable and portable electronics. However, severe shuttle effects, low sulfur conductivity, and especially poor electrode mechanical flexibility restrict sulfur utilization and loading for practical applications. Herein, high‐flux, flexible, electrospun fibrous membranes are developed, which succeed in integrating three functional units (cathode, interlayer, and separator) into an efficient composite. This structure helps to eliminate negative interface effects, and effectively drives synergistic boosts to polysulfide confinement, electron transfer, and lithium‐ion diffusion. It delivers a high initial capacity of 1501 mA h g −1 and a discharge capacity of 933 mA h g −1 after 400 cycles, with slow capacity attenuation (0.069% per cycle). Even under high sulfur loading (13.2 mg cm −2, electrolyte/sulfur ratio = 6 mL g −1 ) or in an alternative folded state, this three‐in‐one membrane still exhibits high areal capacity (11.4 mA h cm −2 ) and exceptional application performance (powering an array of over 30 light‐emitting diodes (LEDs)), highlighting its huge potential in high‐energy flexible devices. Abstract : Integrated "three‐in‐one" electrospun fibrous membranes are developed for flexible and high‐loading lithium–sulfur batteries. This structure can eliminate negative interface effects and effectively drives synergistic boosts to polysulfide confinement, electron transfer and Li + diffusion. As a result, excellent battery performance is achieved even under the high sulfur loading of 13.2 mg cm −2 and an alternative folded state.